Augmenting a dynamic hip screw with a calcium sulfate/hydroxyapatite biomaterial. (June 2021) - Kok, Joeri; Širka, Aurimas; Liu, Yang; Tarasevičius, Šarūnas; Belickas, Juozas; Tägil, Magnus; Lidgren, Lars; Isaksson, Hanna; Raina, Deepak Bushan
Highlights: Calcium sulfate/hydroxyapatite can aid in the fixation of a dynamic hip screw. Fenestrated screws help create a stronger interface between biomaterial and screw. Increased fixation is more evident in low density bone. Biomaterial distribution in the threads is crucial for improving implant fixation. Abstract: Internal fixation failure in hip fractures can lead to reoperation. Calcium sulfate/hydroxyapatite (CaS/HA) is a biomaterial that can be used for augmenting fracture fixation. We aimed to determine whether an injection of 2 ml CaS/HA increases the fixation of a dynamic hip screw inserted in synthetic and human trabecular bone. The study consists of two parts: 1) synthetic bone blocks (n = 74), with three subgroups: empty (cannulated screw, no injection), cannulated, and fenestrated; and 2) osteoporotic human femoral heads (n = 29), with the same subgroups. The heads were imaged using µCT. Bone volume fraction, insertion angle, and head diameter were measured. Pullout tests were performed and peak force, stiffness, and work were measured. The fenestrated group showed increases in pullout strength compared to no injection in the synthetic blocks. The cannulated group showed a higher pullout strength in low-density blocks. In the femoral heads, the variation was larger and there were no significant differences between groups. The bone volume fraction correlated with the peak force and work, and the insertion angle correlated with the stiffness. CaS/HA can improve the fixation of a dynamic hip screw. For clinical use, spreading of the material around the threads of the screw must be ensured.